TEACHER'S BELIEFS ABOUT THE ROLES OF AN ENGLISH LANGUAGE TEACHER: A CASE STUDY OF A NON-ENGLISH EDUCATION GRADUATE TEACHER - Ismi Ajeng Hurriyah, - (2019)
The fact that teachers play a crucial role at school as educators and have significant influence on students' growth has been the main rationale for the conduct of this study. Aiming to better understand teachers' selves and the world in which they operate, this study focuses on one particular case of a teacher who did not graduate from an English education program. Specifically, this study seeks to understand how a teacher with no basic knowledge of English education shapes her beliefs about her roles as an English language teacher and how these beliefs inform her teaching practices. As this research adopts a qualitative case study, which employed in-depth interviews and classroom observations as its main data collection techniques, the research findings and discussion are thus presented in the form of narratives. Apart from Borg's (2006) theory of teachers' beliefs, Richards and Lockhart's (2006) categorization of teachers' roles have been drawn as key theoretical frameworks to analyze the data. The data analysis confirms that beliefs are interchangeable and unfixed in nature, as in the case of the teacher participant who has shown changing beliefs that depend on classroom circumstances. While the participant's beliefs have a significant influence on her classroom practices, classroom observations revealed that sometimes the two were not always consistent. The findings and discussion presented in this study are expected to raise better awareness of the important roles that teachers play and the challenges they face in the classroom.; Fakta bahwa guru berperan penting di sekolah sebagai pendidik dan memiliki pengaruh besar terhadap pertumbuhan siswa telah menjadi alasan utama untuk melakukan penelitian ini. Bertujuan untuk lebih memahami guru dan dunia di mana mereka beroperasi, penelitihan ini berfokus pada satu kasus tertentu dari seorang guru yang tidak memiliki gelar sarjana dari program pendidikan bahasa Inggris. Secara khusus, penelitian ini berupaya memahami bagaimana seorang guru tanpa pengetahuan dasar tentang pendidikan bahasa Inggris membentuk keyakinannya tentang perannya sebagai guru bahasa Inggris dan bagaimana keyakinan ini menginformasikan praktik mengajarnya. Karena penelitian ini mengadopsi studi kasus kualitatif, yang menggunakan wawancara mendalam dan observasi kelas sebagai teknik pengumpulan data utamanya, temuan penelitian dan diskusi disajikan dalam bentuk narasi. Selain dari Borg (2006) tentang teori teachers' beliefs, kategorisasi dari Richards dan Lockhart (2006) tentang peran guru telah diambil sebagai kerangka teoritis untuk menganalisis data. Analisis data menegaskan bahwa beliefs dapat berubah dan tidak tetap, seperti dalam kasus guru yang menunjukkan perubahan beliefs yang bergantung pada keadaan kelas. Sementara beliefs guru tersebut memiliki pengaruh yang besar terhadap praktik di ruang kelasnya, pengamatan di kelas mengungkapkan bahwa keduanya tidak selalu konsisten. Temuan dan diskusi yang disajikan dalam penelitian ini diharapkan dapat meningkatkan kesadaran yang lebih baik tentang peran penting yang dipraktikkan guru dan tantangan yang mereka hadapi di kelas.